Multi-color 2D datamatrix codes with poorly readable colors - Bogataj, Urška; Muck, Tadeja; Lozo, Branka; Žitnik, Arjana (Journal of Graphic Engineering and Design, 2023)
Datamatrix code is a type of 2D codes that can encode much more data on the same or smaller area than the linear barcodes. This makes 2D codes usable for marking even very small items. 2D codes can be decoded by the readers in retails but also with the mobile phones equipped with camera and appropriate software. 2D codes can be depicted in different materials or printed on different printing substrates. The application area of the codes is broad, from magazines and newspapers to posters and packaging. Successful reading of 2D codes is possible if the code is printed in appropriate contrast between the printing ink and substrate, like black ink printed on white matt paper. Problems can occur if the code is printed in colors. The readability of 2D Datamatrix codes printed in cyan, magenta, yellow and black was studied. Yellow is proved to be poorly readable. In addition, the bi-colored and multi-colored 2D Datamatrix codes were studied. When four colors are used in creation of the 2D Datamatrix code, poorly readable elements, yellow codewords, may cause the reading failure. 2D Datamatix codes are capable to ensure good readability even if they contain a defined number of poorly readable codewords due to the Reed – Solomon error-correction system. The aim of the study was to investigate the effect of using yellow printed, poorly readable, codewords in the multi-colored 2D Datamatrix code on the code readability.